Electoral Corruption And Its Birth In Postsoviet Russia - Yu A Nisnevich (RUDN Journal of Political Science, 2014)
In the article there is given the definition of electoral corruption and its institutional mechanism as abuse of administrative resource of public power. The classification of the types of administrative resource of public power is given in the article as well. On the basis of analysis of the Russian electoral model the author discovered how abuse of different types of administrative resources could influence the results of elections. Corruption began to emerge in Russia in electoral cycles of parliament and presidential elections of 1995-1996 and 1999-2000. The operation “the successor” is taken under serious consideration in the article.